(3eLGdS GdCHQGQ heSGdc GdCNjGQs - (3GdbHQSj, GdQhej, CMeO Hf YHO GdbGgQ, J(B1043(3g`s
(3ChdgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde eKd GdPj jPcQ QHg hGdPj dG jPcQ QHg eKd GdMj hGdejJ gPG GdMOjK ef UMGM GdeUGHjM QhGg CHh ehSi GdCTYQjs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3ajdRe GdOhQ hGdJSdSd GdPj gh hLhO MhGOK dG Chd dgG hcdGgeG eMGd hdh de jcf hGMOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 154s
(3eYLe GdeDdajf(B: 1 / 174s
(3cTa GdXfhf(B: 2 / 1590s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs